DNA BARCODING OF Caranx senegallus FROM THREE WATER BODIES ADJOINING THE GULF OF GUINEA, NIGERIA - Eriegha, Ochuko Joshua; Ekelemu, Jerimoth Kesena; Nwachi, Oster Francis (FUDMA Journal of Sciences, 2024)
Fish species show astonishing phenotypic and genetic diversity in populations. The delimitation and recognition of fish species are not only of interest to taxonomists but also a requirement in studies of ecology. In this study, the genetic structure of Caranx senegallus collected from three water bodies adjoining the Gulf of Guinea, Nigeria was characterized using the cytochrome c oxidase I (COI) barcode gene region. Fish samples collected from Qua Iboe estuary, Escravos estuary, and Lagos lagoon were identified morphologically, and muscle tissues were used for DNA barcoding using Fish1 and Fish2 primers. Evolutionary analysis showed the formation of diverging clades in the neighbor-joining tree and indicated the presence of multiple species. The result also revealed that morphological identification was not entirely successful, as the Basic Local Alignment Search Tool (BLAST) prediction confirmed the presence of three specimens initially identified as C. senegallus but genetically matching C. fischeri and Trachinotus goreensis. This observation further emphasized the need for an integrative method for species identification.
Keywords: Biodiversity; Mitochondrial DNA; Phylogenetic diversity; cytochrome c oxidase I; Jackfish